Evolving temperature field in a fossil subduction channel during the transition from subduction to collision (Tauern Window, Eastern Alps). (12th October 2020) - Groß, Philip; Pleuger, Jan; Handy, Mark R.; Germer, Marisa; John, Timm
Abstract: We investigate the evolution of the three‐dimensional thermal structure of a palaeo‐subduction channel exposed in the Penninic units of the central Tauern Window (Eastern Alps). Structural and petrological observations reveal a sheath fold with an amplitude of some 20 km that formed under high‐ P conditions (~2 GPa). The fold is a composite structure that isoclinally folded the thrust of an ophiolitic nappe derived from Alpine Tethys Ocean onto a unit of the distal European continental margin, also affected by the high‐ P conditions. This structural assemblage is preserved between two younger domes at either end of the Tauern Window. The domes deform isograds of the T ‐dominated Barrovian metamorphism that itself overprints the high‐ P metamorphism partly preserved in the sheath fold. Using Raman spectroscopy on carbonaceous material (RSCM), we are able to distinguish peak‐temperature domains related to the original subduction metamorphism from domains associated with the later temperature‐dominated (Barrovian) metamorphism. The distribution of RSCM temperatures in the Barrovian domain indicates a lateral and vertical decrease of peak temperature with increasing distance from the centres of the thermal domes. This represents a downward increase of palaeo‐temperature, in line with previous studies. However, we observe the opposite palaeo‐temperature trend in the lower limb of the sheath fold, namely an upward increase. We interpret this inverted palaeo‐temperature domain as the relic of a subduction‐related temperature field. Towards the central part of the sheath fold's upper limb, RSCM temperatures increase to a maximum of ~520°C. Further upsection in the hangingwall of the sheath fold, palaeo‐peak temperatures decrease to where they are indistinguishable from the peak temperatures of the overprinting Barrovian metamorphism. Peak‐temperature contours of the subduction‐related metamorphism are oriented roughly parallel to the folded nappe contacts and lithological layering. The contours close towards the northern, western and eastern parts of the fold, resulting in an eye‐shaped, concentric pattern in cross‐section. The temperature contour geometry therefore mimics the fold geometry itself, indicating that these contours were also folded in a sheath‐like manner. We propose that this sheath‐like pattern is the result of a two‐stage process that reflects a change of the mode of nappe formation in the subduction zone from thrusting to fold nappe formation. First, thrusting of a hot oceanic nappe onto a colder continental nappe created an inverted peak‐thermal gradient. Second, sheath folding of this composite nappe structure together with the previously established peak‐temperature pattern during exhumation. This pattern was preserved because temperatures decreased during retrograde exhumation metamorphism and remained less than the subduction‐related peak temperatures during the later Barrovian overprint. The fold ascended with diapir‐like kinematics in the subduction channel.